Association of Insight, Age, and Education Level with Relapse Rates in Schizophrenia Patients - Rahmad Dhani Rujito; Erna Herawati; Sahilah Ermawati; Siti Soekiswati (Warmadewa University, 2026)
Abstract Schizophrenia is a chronic mental disorder with a high tendency for relapse, which worsens the patient's prognosis and increases the burden of care. Clinical factors such as insight, as well as demographic factors including age and education level, are thought to play a crucial role in influencing treatment adherence and relapse risk. This study aims to analyze the association between insight, age, and education level with relapse rates in schizophrenia patients at RSJD dr. Arif Zainudin Surakarta. This was an analytic observational study with a cross-sectional design. Subjects were selected using purposive sampling, totaling 96 patients. Data were analyzed using Chi-Square test, Fisher’s Exact test, and Logistic Regression. The results showed a significant association between insight (p=0.045) and education level (p=0.046) with relapse rates. Meanwhile, age (p=0.588) was found to have no significant association with relapse incidence. It is concluded that insight and education level are associated with relapse rates, although no single factor emerged as a dominant independent predictor in the multivariate model. Improving patient insight through psychoeducation is recommended to prevent relapse.